EMPIRICAL STUDY OF PERSONAL DETERMINANTS OF THE CHOICE OF COPING STRATEGIES OF SERVICEMEN - Yarmolchyk, Maria (International Journal of Innovative Technologies in Social Science, 2021)
Today, the activities of military units become especially important in conditions of instability in the country. Consequently, the study of the psychological characteristics of such people becomes expedient. Modern types of combat are requirements that often exceed the capabilities and resources of the military. This, in turn, creates a need for a special type of personality - stable, socially active, with a high level of self-regulation and the ability to withstand pressure from adverse factors [9]. In modern psychology, the individual way in which a person can cope with a complex, crisis situation is determined by the concept of coping behavior. The study of this concept is especially relevant for persons working in the Armed Forces of Ukraine. Coping is a strategy of behavior in complex stressful situations, which is chosen by servicemen to deal with stress. This is a kind of response of the psyche, which is an adaptive mechanism at the time of negative impact. The choice of coping strategies is determined by a number of personality traits that determine the dominant pattern of behavior of a particular serviceman during decompression.